2012
DOI: 10.1371/journal.pone.0032517
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Object Directed and Non-Object Directed Action in the Human Mirror System; Implications for Theories of Motor Simulation

Abstract: Mirror neurons are single cells found in macaque premotor and parietal cortices that are active during action execution and observation. In non-human primates, mirror neurons have only been found in relation to object-directed movements or communicative gestures, as non-object directed actions of the upper limb are not well characterized in non-human primates. Mirror neurons provide important evidence for motor simulation theories of cognition, sometimes referred to as the direct matching hypothesis, which pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 53 publications
2
21
0
1
Order By: Relevance
“…Our results showed that, observing actions of the “touch” condition (vs. no‐touch) activated both PMv and SI/SII, suggesting that vicariously experiencing a product involved sensory‐related activity for tactile sensations as well as motor‐related activity for hand movements in bilateral MNS. These results are consistent with previous findings that the premotor and parietal network were preferentially active during object‐directed actions, rather than during non‐object‐directed actions [Agnew et al, ]. Moreover, vicarious neural responses were positively correlated with self‐reported purchasing intention.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that, observing actions of the “touch” condition (vs. no‐touch) activated both PMv and SI/SII, suggesting that vicariously experiencing a product involved sensory‐related activity for tactile sensations as well as motor‐related activity for hand movements in bilateral MNS. These results are consistent with previous findings that the premotor and parietal network were preferentially active during object‐directed actions, rather than during non‐object‐directed actions [Agnew et al, ]. Moreover, vicarious neural responses were positively correlated with self‐reported purchasing intention.…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have directly investigated whether components of the network are modulated specifically by the presence or absence of an object [Hétu, Mercier, Eugène, Michon, & Jackson, ; Koski et al, ; Turella, Tubaldi, Erb, Grodd, & Castiello, ]. Most examining “transitivity” tend to confound object presence with “meaning,” comparing actions performed with objects to meaningless actions [e.g., Agnew, Wise, & Leech, ; Menz, McNamara, Klemen, & Binkofski, ] or comparing pantomimed actions to communicative gestures [e.g., Corina, Chiu, Knapp, Greenwald, San Jose‐Robertson, & Braun, ; Montogomery, Isenberg, & Haxby, ]. Evidence gleaned indirectly from studies that include object‐directed actions and similarly matched nonobject‐directed actions (i.e., pantomimes) hint that components of the AON may be sensitive to observing a person perform an action with or without an object.…”
Section: Introductionmentioning
confidence: 99%
“…4,43 In the present study, it was assumed that the mirror neuron response would be better for task-based movements than for non-task-based movements in MT. 12,13 The neurons fire during subjects' actual performance and when they are merely watching the similar motor tasks in the mirror, which helps in the learning of new skills by visuomotor-proprioception inputs. 44,45 Clinically, reduction in the awkwardness and improvement in speed and accuracy of the entire upper extremity movements were observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The human mirror neuron response is signifi cantly greater for taskbased movements. 12,13 Task-specific training, which is a goal-directed repetitive practice of motor tasks, has been found to enhance positive cortical reorganization and motor recovery in poststroke patients. [14][15][16] Out of various motor therapies, MT proved to be potentially benefi cial in poststroke hemiparesis.…”
mentioning
confidence: 99%